1984
DOI: 10.1111/j.1432-1033.1984.tb08446.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular transport of the major glycoprotein of zymogen granule membranes in the rat pancreas

Abstract: The intracellular transport and destination of the major glycoprotein associated with zymogen granule membranes in the pancreas (GP-2) was established. In suspensions of isolated acinar cells from rat pancreas, pulsechase experiments were performed. The incorporation of the first newly synthesized GP-2 molecules into zymogen granule membranes occurred at about 60 min after beginning of the pulse. We demonstrated by using two different methods that newly made GP-2 reaches the cell surface within the same time s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
(12 reference statements)
1
13
0
Order By: Relevance
“…Pulse-chase studies with dissociated rat pancreatic cells by Havinga et al (15,16) have indicated that GP-2 is a 73-kDa species in the rough endoplasmic reticulum (0-40 min of chase) and a 78-to 80-kDa species in the Golgi compartment and ZGs (60 min of chase), findings consistent with the N-linked-glycoprotein nature of GP-2 and the addition of terminal sugars within the Golgi apparatus. With longer chase periods (4-6 hr), GP-2 assumed a slightly smaller size (75 kDa), and this form was observed in a plasma membrane fraction and in the medium bathing acinar cells.…”
supporting
confidence: 54%
“…Pulse-chase studies with dissociated rat pancreatic cells by Havinga et al (15,16) have indicated that GP-2 is a 73-kDa species in the rough endoplasmic reticulum (0-40 min of chase) and a 78-to 80-kDa species in the Golgi compartment and ZGs (60 min of chase), findings consistent with the N-linked-glycoprotein nature of GP-2 and the addition of terminal sugars within the Golgi apparatus. With longer chase periods (4-6 hr), GP-2 assumed a slightly smaller size (75 kDa), and this form was observed in a plasma membrane fraction and in the medium bathing acinar cells.…”
supporting
confidence: 54%
“…GP-2 has been localized in pancreatic acinar cells in transGolgi, condensing vacuoles, ZGs (spherical particles, =1000 nm), and apical plasma membranes (7)(8)(9)(10)21). Using similar methods, THP has been localized in kidney TALH cells in trans-Golgi, apical vesicles (oblong structures, 30-150 nm), and apical plasma membranes (42,43).…”
Section: Methodsmentioning
confidence: 99%
“…Since these early experiments, Havinga et al [35] have also demonstrated that a fraction of glyco protein-2 (GP2) molecules, a major zymogen granule membrane protein also found in Golgi apparatus, is transported to the plasma membrane by a route distinct from the one followed by the mass of the newly synthe sized zymogens. It was later found that un der resting conditions newly synthesized se cretory proteins come out of the cell in two waves [36,37].…”
Section: Alternative Route For the Release Of Secretory Proteins Undementioning
confidence: 99%